PRIORITY RIGHTS IN THE PROCESS OF CONVERTING EIGENDOM VERPONDING LAND INTO PROPERTY RIGHTS: A JURIDICAL ANALYSIS: Case Study of Decision Number: 337/Pdt.P/2013/Pn.Jr - Firmansyah, Rendy; Permanasari, Lolita (YURIS: Journal of Court and Justice, 2022)
The land ownership by an individual or a group have right to freely use it. According to the philosophy of customary law, rights are the authority, power and ability of people to act on objects. There are many cases of ex-western land rights that have not been converted after 20 years of the UUPA has been in force. For instance, a case that occurred is the ex-western land of Eigendom Verponding number 3529 in Jember district. The judge has tried to determine. The main problem of this study is the way to recognize and prioritize priority rights in the process of converting Eigendom land into property rights. Juridical analysis used to examine the priority rights in the process of converting Eigendom Verponding land into property rights (case study of case determination no. 337/pdt.p/2013/pn.jr). This problem was studied using a normative method, with a case approach and legislation. The conclusion of this study is that priority rights are used in solving land problems to obtain land rights, determine ownership rights, obtain compensation due to the abolition or cessation of land use and utilization rights, and determine the subject of rights who have the right to manage the land properly.